Perimenopausal Stress Reactions: A Qualitative Study on the Awareness of Spouses - G Nair, Ammu; George , Sonia (East European Journal of Psycholinguistics, 2021)
The menopausal transition can be a period of stress, even lead to trauma if left unnoticed or unsupported. Perimenopause is considered to be the period (3-8 years) before and after the final menstrual cycle. It is a phase in a woman’s life that needs immense support and care from the spouse. But still, researchers are sceptical about the information men have regarding the period. Even though many studies highlight the physiological changes that happen during the perimenopausal or menopausal transition period, there is still a lack in the number of studies that emphasize the psychological difficulties women face in the perimenopausal period. Emotional support from the husband is of significance amid many such difficulties. The study intends to investigate the level of awareness men have about the perimenopausal period.The study also tries understand how the spouses perceive themselves to have supported their wives during the perimenopausal period. The study followed a qualitative approach in data collection and analysis. The data was collected using a semi-structured interview. 34 men (spouses of perimenopausal women) from Thiruvananthapuram, Ernakulam, and Thrissur districts of Kerala, India were selected using purposive sampling. The method of thematic analysis was used to analyze the data. For the analysis, the software NVivo was used. The final themes extracted were unawareness, attitude, regret, and techniques to be adopted. The results revealed the unawareness majority of the participants had about the phase and throw light on the need to create awareness among men to help women cope better with the phase. The major reasons, the participants noted as reasons for their unawareness, were lack of information from the family, lack of communication from their spouses, which led to major confusion in them.